2012
DOI: 10.1134/s2070205112020074
|View full text |Cite
|
Sign up to set email alerts
|

Wave sorbostriction: Waves of adsorption deformation of microporous adsorbent

Abstract: A new phenomenon is discovered: waves of adsorption deformation or wave sorbostriction of a microporous adsorbent appearing under passage of individual compounds or mixtures thereof in a flow of a carrier gas through it. The method of wave sorbostriction registration is suggested. It is found that the wave amplitude and selectivity of adsorbent sorbostriction depend largely on the mixture composition and physi cochemical properties of its components. The suggested method is used to obtain sorbostriction waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The wavelike changes in geometrical dimensions of a microporous selective adsorbent, that is, a phenomenon of wave sorbostriction, should also be mentioned. This effect can be considered a specific manifestation of adsorption-induced deformation observed under dynamic conditions when individual substances or mixtures in a carrier gas flow through the porous material. , When studying the variations in the dimensions of a microporous carbon adsorbent during the passage of normal hydrocarbons ( n -pentane and n -heptane) and their mixtures in the flow of He, Fomkin et al found that the wave amplitude and selectivity depended on the mixture composition and physicochemical properties of its components. Moreover, the wave sorbostriction can potentially be applied to analyze the chemical composition of gas mixtures in NG and oil processing…”
Section: Introductionmentioning
confidence: 99%
“…The wavelike changes in geometrical dimensions of a microporous selective adsorbent, that is, a phenomenon of wave sorbostriction, should also be mentioned. This effect can be considered a specific manifestation of adsorption-induced deformation observed under dynamic conditions when individual substances or mixtures in a carrier gas flow through the porous material. , When studying the variations in the dimensions of a microporous carbon adsorbent during the passage of normal hydrocarbons ( n -pentane and n -heptane) and their mixtures in the flow of He, Fomkin et al found that the wave amplitude and selectivity depended on the mixture composition and physicochemical properties of its components. Moreover, the wave sorbostriction can potentially be applied to analyze the chemical composition of gas mixtures in NG and oil processing…”
Section: Introductionmentioning
confidence: 99%